In vitro propagation and callus induction of medicinal endangered plant meadow rue (Thalictrum minus L.) for producing berberine - Zahra Sargazi Moghadam; Nasrin Moshtaghi; Ahmad Sharifi; Asma Zahedi; Azade Khadem (Institue of Medicinal Plants, ACECR, 2022)
Background: Thalictrum minus L. is a medicinal plant contains berberine, which is used for complementary treating of some diseases. Excessive harvesting of this species from rangelands to extract the alkaloid has endangered its survival. Objective: This study was aimed for in vitro propagation of this species and berberine production. Methods: The seeds were germinated at in vitro culture conditions. Then, the leaves were used as explants for callus induction in two MS and LS basal media supplemented with BA (0, 0.1, 0.5 and 1 mg/L) in combination with different concentrations of auxins, NAA, 2,4-D or IAA. Results: The results showed that MS medium with the plant growth regulator combination of 0.5 mg/L BA and 0.5 mg/L NAA had the highest callus formation and 100 % regeneration. Some calli were transferred to three liquid culture media (MS, LS, or ½ MS) with 1 mg/L BA + 0.1 mg/L NAA or without plant growth regulator to produce the berberine. The HPLC results identified 6 % of berberine in the liquid medium. This amount of berberine can be easily released into the culture medium, therefore, it will be easier to extract.  Conclusion: This method can be successfully used for propagation and extraction of berberine without plant destruction.